Paraoxonase 1 192 and 55 polymorphisms in nephrotic children - ALPAY, HARİKA; YILDIZ, NURDAN (SPRINGER, 2006)
Human paraoxonase 1 (PON1) is a serum enzyme related to high-density lipoprotein which has a major role in preventing oxidative modification of low-density lipoprotein. Due to its amino acid substitution PON1 has two genetic polymorphisms. These polymorphisms are characterized by the location of glutamine (A genotype) and arginine (B genotype) at position 192, and leucine (L genotype) and methionine (M genotype) at position 55. Hyperlipidemia and increased lipid oxidation in nephrotic syndrome may lead to glomerulosclerosis and progression of the glomerular disease. In this study we aimed to investigate PON1 192 and PON1 55 polymorphisms in children with focal segmental glomerulosclerosis (FSGS) and control subjects. The study included 25 children with biopsy-proven FSGS and 30 healthy controls. We demonstrated a statistically significant difference between FSGS patients and control subjects with respect to the distribution of the PON1 polymorphism. The AA genotype was less frequent and the AB+BB genotype was more frequent in FSGS patients than in controls (48 versus 73% for AA genotype and 52 versus 27% for AB+BB genotype, p < 0.05). Distributions of PON1 55 genotypes of FSGS and control subjects were also statistically different (76 versus 43% for LL genotype and 24 versus 57% for LM+MM genotype, p < 0.05) (case-control study, dominant model, Fisher's exact test). The distributions of both genotypes in subgroups of FSGS (stable renal function versus declining renal function) were not statistically different. We conclude in this preliminary study that presence of B allele and/or L allele may be risk factors for the development of FSGS in children.
Keywords: paraoxonase 1 192 polymorphism; paraoxonase 1 55 polymorphism; nephrotic syndrome; child; FOCAL SEGMENTAL GLOMERULOSCLEROSIS; CORONARY-HEART-DISEASE; MOLECULAR-BASIS; RISK; DNA